Finanzielle Grundbildung Programme und Angebote planen - Mania, Ewelina (Perspektive Praxis, 2015)
"Competence in the handling of money is an essential, every-day competence. Until now, however, there were no didactic concepts for the area of basic financial education. The handout provided here introduces a competence model that systematises and describes the (action) requirements for handling money. Various practical applications are illustrated and concrete offering formats are presented. On the basis of three good practice examples, practice-oriented aids complete with exercises and checklists for the development and implementation of study offers are provided. The handout is rounded off with strategies for the successful address and acquisition of target group members."